PERBEDAAN KEMANDIRIAN BELAJAR DAN HASIL BELAJAR DESAIN GRAFIS PERCETAKAN KARENA PENGARUH MODEL PEMBELAJARAN CBL DAN PBL BERBANTUAN VIDEO TUTORIAL PADA SISWA KELAS XI MULTIMEDIA SMK NEGERI 1 GEMPOL - Ruhul Hardiana Sari (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2019)
The purpose of the research is to reveal the contribution of Independence Students and Learning Facilities Availability against the Result of Wireless Network Study of Students of Computer and Network Engineering in SMKN 8 Malang. The result of the study were obtained from the skill competence and knowledge competencies. This research used expost facto method. Type and data analysis of the research is using a quantitative approach with a sample of the research amounted to 95 students XII Computer And Network Engineering in Vocational High School 8 Malang. Data collection for independece and learning facilities is using quetionnaire, while data collection for result of the study is using value documentation. Data analysis included descriptive and regression. The result of the research showed that: (1) independence students contributed to the skill competence amounted to 14,1%, (2) independence students contributed to the knowledge competence is amounted to 19%, (3) learning facilities availability contributed to the skill competence is amounted to 23,5%, (4) learning facilities availability contributed to the knowledge competence is amounted to 7%, (5) independence students and learning facilities are jointly contribute to the skill competence by 25,6% and (6) independence students and learning facilities are jointly contribute to the knowledge competence by 19,2%.